The quest of the missing map - Keene, Carolyn (New York : Grosset & Dunlap, 2007)
The eighteen-year-old girl detective must find a man who has been missing for years in order to locate the other half of a treasure map.
With: Mystery of the moss-covered mansion, by Carolyn Keene. New York, Grosset & Dunlap, 1971.
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Treasure-troves -- Fiction; Buried treasure -- Fiction; Detective and mystery stories, American